2012
DOI: 10.1177/1074248411431581
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Attenuates Cardiac Fibrosis and Hypertrophy in a Rat Model of Diabetic Nephropathy

Abstract: Pioglitazone has been demonstrated to have beneficial effects on cardiovascular outcomes. However, little is known about its effect on cardiac remodeling associated with diabetic nephropathy. Therefore, this study was designed to study the effects of pioglitazone on cardiac fibrosis and hypertrophy in a rat model of diabetic nephropathy. For this purpose, male Wistar albino rats were randomly assigned into 4 groups (n = 10 per group): normal (N) group, diabetic (D) group, diabetic nephropathic (DN) group recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…We speculate that the anti-fibrotic effect of pioglitazone mediated by the miR-711 pathway occurs in a PPAR-dependent manner. A vast amount of data from recent years suggested that the anti-fibrotic effects of pioglitazone mediated by PPAR occur by various mechanisms, including control of inflammation [11], cross-regulation of signaling events implicated in fibrogenesis [12][13][14], reducing oxidative stress-induced NAPDH oxidase-mediated ROS activity [13], and impacting on the key molecules involved in both inflammation or fibrosis, such as, NF-B [15]. In light of these mechanisms, the effects of the pioglitazone-miR-711 pathway on inflammatory cells, fibrogenesis, molecular signaling and ROS require further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the anti-fibrotic effect of pioglitazone mediated by the miR-711 pathway occurs in a PPAR-dependent manner. A vast amount of data from recent years suggested that the anti-fibrotic effects of pioglitazone mediated by PPAR occur by various mechanisms, including control of inflammation [11], cross-regulation of signaling events implicated in fibrogenesis [12][13][14], reducing oxidative stress-induced NAPDH oxidase-mediated ROS activity [13], and impacting on the key molecules involved in both inflammation or fibrosis, such as, NF-B [15]. In light of these mechanisms, the effects of the pioglitazone-miR-711 pathway on inflammatory cells, fibrogenesis, molecular signaling and ROS require further exploration.…”
Section: Discussionmentioning
confidence: 99%
“… The TFG group: This group received an intragastric injection of TFG extract (1000 mg/kg/day)[ 15 ] The Pioglitazone group (Pio): This group received intragastric injection of pioglitazone (10 mg/kg/day)[ 16 ] The Diabetic control group (Con): This group was used as an insulin-resistant control group and did not receive any injections. …”
Section: Methodsmentioning
confidence: 99%
“…COX-2 inhibitors attenuated AngII-induced oxidative stress, hypertension and cardiac hypertrophy in rats [26]. Meanwhile, a specific peroxisome proliferator-activated receptor γ (PPAR-γ) ligand, such as pioglitazone, could decrease cardiac fibrosis and improve left ventricular diastolic dysfunction [27,28] by downregulating the activity of the RAS in the diabetic myocardium [29]. Therefore, increased COXs and decreased PPAR-γ could lead to cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%